Wushu Athlete Physical Fitness - Nabila; Destriani; Destriana (Journal of Physical Education Health and Sport, 2025)
Wushu is a martial arts sport that originates from China and is starting to develop in Indonesia. Wushu activities as a whole in Indonesia have been stopped due to the COVID 19 pandemic, causing many athletes to be unable to display their best abilities. As evidenced by training at Jakabaring Sport City (JSC), athletes quickly get tired due to lack of training activities, which also results in poor body condition. To achieve maximum performance, an athlete must definitely have good physical fitness. In this research, we used the Indonesian Student Fitness Test which consists of Body Mass Index (BMI), Sitting Reach Test V, Sit Up Test 60 seconds, Squat Push Test 30 seconds, and Pacer Test with descriptive research to determine the level of fitness of student athletes from the Garuda Wushu Melati Putih Palembang club. Based on observations during the research, there were several Wushu athletes at the Garuda Melati Putih Palembang club who were not fit enough, so that when taking the test the athletes had difficulty carrying out these movements. Obtained from 29 Wushu athletes from the Garuda Melati Putih Palembang club, 25 athletes were in the very good category (86,2%), 2 athletes were in the fair category (0,68%), 1 athlete was in the poor category (0,3%), and the remaining 0 athletes (0%). It was concluded that the Indonesian Student Fitness Test of the Garuda Wushu Melati Putih Palembang club still showed very good criteria.